Epigenetic modifications and improved regulatory T-cell function in subjects undergoing dual sublingual immunotherapy - Swamy, Ravi S.; Reshamwala, Neha; Hunter, Tessa; Vissamsetti, Soujanya; Santos, Carah B.; Baroody, Fuad M.; Hwang, Peter H.; Hoyte, Elisabeth G.; Garcia, Marco A.; Nadeau, Kari C. (Journal of allergy and clinical immunology, 2012)
Allergen-specific immunotherapy is the only mode of therapy that has been demonstrated to offer a cure in patients with IgE-mediated respiratory allergies. We sought to demonstrate the safety and efficacy of timothy grass (TG) and dust mite (DM) dual sublingual immunotherapy (SLIT) and to begin to investigate the immune mechanisms involved in successful immunotherapy with multiple allergens. The safety and efficacy of dual SLIT with TG and DM in children and adults with demonstrated allergies to TG and DM were investigated in a single-center, randomized, double-blind, controlled phase I study. Thirty subjects received either TG and DM dual SLIT (n = 20) or placebo (n = 10). Immune parameters were evaluated for differentiation of desensitized subjects from control subjects. Subjects treated with dual SLIT had decreased rhinoconjunctivitis scores (P < .001) and medication use scores (P < .001) and reduced responses to TG and DM allergen based on results of skin prick tests or nasal disk challenges (P < .01 and P < .001, respectively) compared with placebo-treated control subjects. An increase in TG- and DM-specific IgG4 levels, reduced allergen-specific IgE levels, and subsequent basophil activation were observed in the active treatment group. Dual SLIT promoted allergen-specific suppressive CD4+CD25highCD127lowCD45RO+ forkhead box protein 3 (Foxp3)+ memory regulatory T cells with reduced DNA methylation of CpG sites within the Foxp3 locus. The results of this pilot study suggest that dual SLIT could be an effective means to treat subjects with sensitivities to a variety of allergens and that long-term tolerance might be induced by epigenetic modifications of Foxp3 in memory regulatory T cells.